The Impact of Formal and Informal Pronouns of Address on Product Price Estimation - Helen de Hoop; Ward Boekesteijn; Martijn Doolaard; Niels van Wel; Lotte Hogeweg; Ferdy Hubers (Languages)
Previous literature has examined the effect of using a formal or informal second-person pronoun on consumers’ appreciation of an advertisement and the advertised product and their purchase intention. This is the first study that additionally examines the effect of the use of either pronoun on product price estimation. In a between-subjects web experiment, Dutch participants evaluated product ads in which either an informal or formal pronoun of address was used, or no pronoun of address at all (the control condition). Dependent variables were attitude towards the ad and the product, purchase intention, and price estimation. The results show that the use of the formal pronoun leads to a higher estimate of the price of the advertised product, while a higher price estimate may increase the purchase intention.